Aligning Soft Skills in Requirements Engineering Between Academia and Industry: A Pilot Study - Valle, Rômulo Antônio; Souza, Alinne Cristinne Corrêa; Valle, Pedro Henrique Dias (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES); 2025: Anais do X Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software, 2025)
The Requirements Engineering (RE) process is crucial for the success of software projects, as it establishes the foundation for developing efficient systems aligned with the needs of end users and stakeholders. In this context, soft skills play a fundamental role, being as valued as technical skills due to their impact on the success of software projects. This article aims to map and categorize the soft skills commonly cited in academia and industry concerning the RE process in software development in light of the perspectives of the CHAOS Report: Beyond Infinity. For this, a pilot study was carried out to validate the interview protocol that will be conducted. The main contributions of this study were identifying essential soft skills for RE practices, analyzing soft skills concerning CHAOS Report: Beyond Infinity, and categorizing the mapped skills.